Analysis of the Behavior of Young Couples in Buying a House Using Sharia Contracts - Rinaldy, Salwa Afronisa Aulia; Fadhliah, Syifa; Rasyid, Muhammad Irfan; Nurhayati, Gita; Putra, Purnama (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2024)
This study aims to analyze the direct and indirect influence among variables such as attitudes, subjective norms and behavioral control perceptions on the decision-making of young couples in buying houses based on sharia contracts with interest variables as the intervening variable. This study used a quantitative method used by distributing questionnaires to 250 young couples. This study used a side purposive sampling method. This study applied a a path analysis to examine the direct and indirect influence of independent variables on dependent variables through intervening variables. The results of the study showed that attitudes, subjective norms and perception of behavioral control influenced people’s interests to buy a house using sharia-based contracts. Furthermore, attitudes affect decision-making, while subjective norm variables and behavioral control perceptions do not have a significant effect on decision-making. Nevertheless, interests have a positive and significant effect on decision-making. Based on the results of the path analysis, interests could mediate attitudes, subjective norms and perception of behavior control in making decisions in taking houses based on sharia contracts. The results of this study imply that sharia-based banks in Indonesia need to provide a continuous literacy program toward sharia-based mortgage products to increase customers’ interests so that they know the advantages of using sharia-based banks, especially in terms of house mortgage financing products.